2012
DOI: 10.1038/gt.2012.68
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cytotoxicity of oncolytic reovirus in combination with cisplatin–paclitaxel doublet chemotherapy

Abstract: Oncolytic reovirus is currently under active investigation in a range of tumour types. Early phase studies have shown that this agent has modest monotherapy efficacy and its future development is likely to focus on combination regimens with cytotoxic chemotherapy. Indeed, phase I/II clinical trials have confirmed that reovirus can be safely combined with cytotoxic drugs, including a platin—taxane doublet regimen, which is currently being tested in a phase III clinical trial in patients with relapsed/metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 24 publications
0
50
0
2
Order By: Relevance
“…Reovirus has also demonstrated efficacy in chemotherapeutic combinations in tumor models of head and neck cancer. Relative to reovirus monotherapy, combination treatment with reovirus, paclitaxel, and cisplatin significantly increased survival in nude mouse tumor model of Cal27, a human cell line from tongue epithelium (49). Importantly, the authors report that there was no increased cytotoxicity produced by the combination platin-taxel chemotherapy and reovirus.…”
Section: Combination Chemotherapymentioning
confidence: 94%
“…Reovirus has also demonstrated efficacy in chemotherapeutic combinations in tumor models of head and neck cancer. Relative to reovirus monotherapy, combination treatment with reovirus, paclitaxel, and cisplatin significantly increased survival in nude mouse tumor model of Cal27, a human cell line from tongue epithelium (49). Importantly, the authors report that there was no increased cytotoxicity produced by the combination platin-taxel chemotherapy and reovirus.…”
Section: Combination Chemotherapymentioning
confidence: 94%
“…Hablando específicamente de la oncoterapia viral en la leucemia, al haber pocos estudios experimentales aún en I I I I II II II II II II II II IT IP IV IV IV IV IV IV IV IV IV IV IV [26][27][28][29][30][31][32][33][34][35][36][37][38][39] . Por estas razones, el reovirus debe ser el virus modificado utilizado en la oncoterapia para la leucemia.…”
Section: Reovirus La Opción En La Leucemiaunclassified
“…Interestingly, these combination studies revealed that the use of reovirus along with common chemotherapeutic agents, such as cisplatin, docetaxel, or cisplatin-paclitaxel doublet chemotherapy or radiotherapy, had synergistic effects in vitro and in vivo. [21][22][23],45] For example, a study conducted by Sei et al investigated the in vitro combination effects of reovirus with a variety of chemotherapeutic agents (cisplatin, gemcitabine, vinblastine, and paclitaxel) against human non-small-cell lung cancer (NSCLC) cells. [25] Additionally, strong synergistic effects were observed only in those cell lines that were sensitive to monotherapy of the respective chemotherapeutic agent.…”
Section: Preclinical Studies With Reovirusmentioning
confidence: 99%